REPRESENTASI ORIENTALISME ASIA DALAM FILM CRAZY RICH ASIANS (Am I really Asian if I'm not Chinese?) - Koesni Jannah, Soraya; Budi Lestari, Sri (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
Film as a cultural product not only has inherited values and meanings, but also in the same time able to provide a picture of the culture and the role of each character that emerges. The formation of stigma about Asian characters that have been displayed often only looks at some viewpoints and does not generally represent the meaning of Asia itself. The aims of this research are to find out and analyze the narrative structure in Crazy Rich Asians movie’s and see how Asia is represented through Western point of view. Using a qualitative approach and a semiotic research method that refers to the semiotic theory of The Codes of Television by John Fiske who sees signs through three levels; reality, representation and ideology. Data was conducted by observing and interpreting the signs and symbols that was contained in the film of Crazy Rich Asians. The unit of analysis in this study is in the form of paradigms and syntagsm found at the level of reality, the level of representation, the level of ideology. The study concluded that Crazy Rich Asians film still used Western Orientalism`s point of view to identify the East by depicting Asian characters as Chinese ethnics, where there is still an assumption that Western culture is superior to Eastern culture which considered traditional and conservative. Like other Hollywood films, the director seems to agree with Asian stereotypes such as yellow skin, speaking using